Association of Physical Activity with Co-morbid Conditions in Geriatric Population - Aliya Hisam; Mahmood Ur Rahman; Rimsha Khan; Sundus Ilyas; Anosha Jabbar; Syed Awais Kazmi; Umer Mushtaq (International Journal of Public Health Science (IJPHS), 2016)
To find out association of physical activity with co-morbid conditions in geriatric population, a cross-sectional study was conducted in different cties of Pakistan in 2015. A total of 114 participants were inducted by non-probability convenience sampling technique. Data was collected after informed verbal consent by a validated questionnaire that is Rapid Assessment of Physical Activity (RAPA). Participants were categorized into two groups i.e. physically active and physically inactive.  Data was entered and analyzed in SPSS version 20. There were 66 (57.9%) males and 48 (42.1%) females with mean age of 57.04±7.348 years. Among hypertensive individuals (n=43, 37.7%) there were 39 (90.7%) physically inactive, among individuals having angina (n=17, 14.9%) there were 15 (88.2%) physically inactive. Out of 37 (32.5%) diabetics, 35 (94.6%) were physically inactive. Among individuals suffering from arthritis (n=40, 35.1%), there were 38 (95%) physically inactive. A significant association was found between physical activity and diabetes and arthritis with p-value of 0.048 and 0.029 respectively. Physical activity is significantly associated with diabetes and arthritis in geriatric population. Adequate physical activity should be performed to reduce the risk of co-morbid conditions and improve the quality of life in geriatric population.